Grenada. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Trinidad and Tobago Delegation of 2022 are identified, focus to needs and interests of the country such as; supported the evaluating of safeguarding systems through an analysis of the National Emergency Response Plan (ERP) that deals with the tomato leaf miner, about better equipped to activate a full-scale response should pests of this nature; collaborated to conduct the first training session on a composting site that was established in 2021 at the CARDI Field Station; beekeepers strengthened their capacities through a workshop on queen bee rearing, disease management, and monitoring of queen bee stock; also, implemented a training course on animal husbandry to extension officers and farmers.